MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SEKOLAH DASAR PADA MATERI BANGUN RUANG DENGAN ALAT PERAGA KERTAS LIPAT - Juhria . (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2020)
INCREASING ACTIVITY AND LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS  ON LESSONS OF GEOMETRY WITH FOLDING PAPER PROPSThis study aims to determine the increase in activity and student learning outcomes, describe the process of increasing student activity and learning outcomes, and measure the magnitude of the increase in activity and learning outcomes in the lessons of building space. The use of folding paper props in class IV SD Negeri Lawang Gintung 2 Bogor City year 2019/2020 lessons. This research is a Classroom Action Research by providing action on research subjects in two learning cycles. The results of this study indicate that using folding paper props can be a fun variation of learning for students so that it is proven to improve student learning outcomes. Before using folding paper props the learning outcomes of students only reached an average value of 64.25 then an increase occurred after using folding paper props to 76.34 in cycle 1 and 97.24 in cycle 2. So it can be concluded that the use of props folding paper is very popular with students and there is an increase in student learning outcomes. Therefore the researchers suggest that the use of folding paper props be socialized and used as an alternative in learning mathematics in schools